MODEL KEPATUHAN MEMBAYAR PAJAK UMKM DI KOTA KEDIRI - Renata, Felicia; Tohari, Amin; Kurniawan, Andy (UNIKA Santo Thomas, 2024)
The purpose of this research is to determine the impact of tax understanding, tax sanctions, tax rates, tax services, also tax knowledge on the compliance of MSME taxpayers in Kediri City in paying taxes. This research uses a quantitative approach with causal associative research techniques. The sample used in this research was 100 MSME taxpayers in Kediri City and was analyzed using the PLS approach using SmartPLS-4.0 software. The conclusion of this research is that tax understanding and tax services do not have a significant impact on the compliance of MSME taxpayers in paying taxes. While tax sanctions, tax rates, also tax knowledge have a significant impact on the compliance of MSME taxpayers in paying taxes